2014
DOI: 10.1016/j.tem.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Ketone bodies as signaling metabolites

Abstract: Traditionally, the ketone body β-hydroxybutyrate (βOHB) has been looked upon as a carrier of energy from liver to peripheral tissues during fasting or exercise. However, βOHB also signals via extracellular receptors and acts as an endogenous inhibitor of histone deacetylases (HDACs). These recent findings support a model in which βOHB functions to link the environment, in this case the diet, and gene expression via chromatin modifications. Here, we review the regulation and functions of ketone bodies, the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
703
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 776 publications
(719 citation statements)
references
References 140 publications
(195 reference statements)
13
703
1
2
Order By: Relevance
“…The production of ketone bodies, or ketogenesis, mainly occurs in the liver where acetyl-CoA is first converted to AcAc, which is further catalyzed by β-hydroxybutyrate dehydrogenase (BDH1) to produce β-HB. While acetone is unable to be further metabolized to produce ATP, both AcAc and -HB are exported into bloodstream and consumed by extra-hepatic tissues, such as muscle, kidney or brain [11]. Of note, ketone bodies are also able to pass through the blood-brain barrier, entering the brain to serve as a major energy source during starvation [12].…”
Section: Introductionmentioning
confidence: 99%
“…The production of ketone bodies, or ketogenesis, mainly occurs in the liver where acetyl-CoA is first converted to AcAc, which is further catalyzed by β-hydroxybutyrate dehydrogenase (BDH1) to produce β-HB. While acetone is unable to be further metabolized to produce ATP, both AcAc and -HB are exported into bloodstream and consumed by extra-hepatic tissues, such as muscle, kidney or brain [11]. Of note, ketone bodies are also able to pass through the blood-brain barrier, entering the brain to serve as a major energy source during starvation [12].…”
Section: Introductionmentioning
confidence: 99%
“…15 The synthesis of ketone bodies, such as β-hydroxybutyrate (βHB) and acetoacetate (AcAc), is controlled by the rate-limiting enzyme, mitochondrial 3-hydroxy-3-methylglutaryl-CoA synthase 2 (HMGCS2). 16 Recently, βHB has also been shown to act as an endogenous inhibitor of HDACs, 17 which are known to regulate intestinal epithelial differentiation. 18 Circulating concentrations of βHB can increase to as much as 6-8 mM during prolonged fasting and caloric restriction 16,17 when the liver switches to fatty acid oxidation, and even to 25 mM in diabetic ketoacidosis.…”
mentioning
confidence: 99%
“…16 Recently, βHB has also been shown to act as an endogenous inhibitor of HDACs, 17 which are known to regulate intestinal epithelial differentiation. 18 Circulating concentrations of βHB can increase to as much as 6-8 mM during prolonged fasting and caloric restriction 16,17 when the liver switches to fatty acid oxidation, and even to 25 mM in diabetic ketoacidosis. These nutritional states are associated with altered intestinal integrity, 19 but it is unknown whether ketone bodies have a role in the maintenance of intestinal homeostasis.…”
mentioning
confidence: 99%
“…KBs in cell culture studies have been demonstrated to act as metabolic inhibitors of glycolytic ATP production and cell growth in several cancer lines [21,22] and also have demonstrable action as signaling molecules with broad cancer inhibiting effects [23][24][25].…”
Section: Rationalementioning
confidence: 99%